2017
DOI: 10.1021/acs.estlett.7b00138
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Organic Carbon/Water Partition Ratios (KOC) of Volatile Methylsiloxanes

Abstract: Knowing the temperature dependence of the organic carbon/water partition ratios (K OC ) of volatile methylsiloxanes (VMS) is required to understand their environmental fate. We measured the K OC of two linear VMS (lVMS), three cyclic VMS (cVMS), and six polychlorinated biphenyls (PCBs) at 25, 15, 10, and 5 °C and calculated their enthalpies and entropies of sorption to organic carbon (ΔH OC and ΔS OC , respectively). The ΔH OC of VMS ranged from −79.2 to −45.8 kJ mol −1 , while the ΔH OC of the PCBs ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…Environmental Science: Processes & Impacts Paper scenarios using the K OC measurements of Kozerski et al, 26 the residence times were all shorter than in scenarios using the measurements of Panagopoulos et al 16,17 and in the case where we used the DH OW measurements of Xu and Kropscott, 31 the residence times were very close to the criterion values for persistence in marine sediments. On the other hand, scenarios using the DH OC measurements of Panagopoulos et al 32 had residence times of VMS that exceeded the REACH criterion for marine sediments in all cases except for D 4 , where residence times were almost equal to the residence time of the REACH criterion. 24 Similar results were observed for the overall residence times.…”
Section: Papermentioning
confidence: 89%
See 4 more Smart Citations
“…Environmental Science: Processes & Impacts Paper scenarios using the K OC measurements of Kozerski et al, 26 the residence times were all shorter than in scenarios using the measurements of Panagopoulos et al 16,17 and in the case where we used the DH OW measurements of Xu and Kropscott, 31 the residence times were very close to the criterion values for persistence in marine sediments. On the other hand, scenarios using the DH OC measurements of Panagopoulos et al 32 had residence times of VMS that exceeded the REACH criterion for marine sediments in all cases except for D 4 , where residence times were almost equal to the residence time of the REACH criterion. 24 Similar results were observed for the overall residence times.…”
Section: Papermentioning
confidence: 89%
“…[27][28][29][30] Xu and Kropscott 31 studied the effect of temperature on the partition ratios of VMS between octanol and water (K OW ) and observed that the K OW of VMS decreased with decreasing temperature. In another recent study, 32 we measured the effect of temperature on the K OC of VMS and observed that K OC increased with decreasing temperatures. This difference could result in substantial differences in the modeled environmental fate and the residence times of VMS in aquatic environments at temperatures lower than the reference temperature of K OC measurements.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations